MANUFACTURE TECHNOLOGY AND DETERIORATION OF SOME ARCHAEOLOGICAL POTTERY OBJECTS IN WADI KHARIG IN SOUTH SINAI, EGYPT: CASE STUDY - Dr.Walid Kamel Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Wadi Kharig is one of the most important archaeological sites in south Sinai containing archaeological pottery and rock art dating back to several ages from prehistoric era until new kingdom; it was discovered by Egyptian expedition of south Sinai antiquities. Some methods of examination and analysis were performed on archaeological pottery such as polarized microscope, " PLM", Scanning Electron Microscope with Energy Dispersive of X-Ray Unit "SEM- EDX" and X-Ray Diffraction Analysis" XRD" and Thermal analysis" TGA" to identify mineral composition of pottery objects, additive materials, mineral changes, fabric, manufacture, and interpretation of manifestations of deterioration for archaeological pottery in Wadi Kharig in South Sinai. The research proved that the used clay was Nile clay. Additions were pottery powder "grog", added sand and limestone powder "dolomite". Surface treatment of the first pottery object was slip layer but red wash was used for the second pottery object as one of surface treatment tools. Firing atmosphere of two archaeological pottery objects was an oxidizing atmosphere. The research also demonstrated that damage manifestations of archaeological pottery objects were weakness, fragility, flaking, cracking, gaps, and crystallization of salts such as halite, carbonate and gypsum, in addition to surface deformation by soiling deposits. The research recommends that materials and methods used in treatment of pottery objects (cleaning, salts extraction, consolidation, display and museum storage) should be chosen based on mineral composition, their different properties and their various deterioration manifestations that have been identified by researcher.